Information Coordination: Does Preannouncement Media Coverage Improve Earnings Expectations?* - Xu, Nina (Contemporary Accounting Research, 2023)
ABSTRACT This study examines whether and how media coverage improves price discovery before earnings announcements. Given the broad reach and timeliness of media coverage, understanding its role in forming earnings expectations is important. I posit that the media specialize in searching for and screening news, while institutional investors and financial analysts specialize in interpreting and integrating information. I expect these coordinated efforts to improve earnings expectations and preempt upcoming earnings announcements. Consistent with this prediction, I find (i) preannouncement media coverage is negatively associated with price revaluations during earnings announcements, (ii) preannouncement media coverage is positively associated with institutional investors' information acquisition and financial analysts' forecast frequency, and (iii) institutional information acquisition and analyst forecast activity are two mechanisms by which media coverage preempts upcoming earnings. My main results are robust to short‐window tests and identification concerns. Overall, my findings suggest that media coverage coordinates information efforts and accelerates the incorporation of information in prices, facilitating preannouncement price discovery.